The effectiveness of telemedicine in improving the timeliness and quality of referrals for non-communicable diseases in the archipelagic settings: A scoping review - Diana Yulias; Arlina Dewi (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Referral systems in island regions often experience delays and inaccuracies in non-communicable disease (NCD) cases due to geographic barriers and limited resources. Telemedicine (tele-triage/teleconsultation) has the potential to accelerate referral decisions and improve the quality of clinical information between facilities. Purpose: To map the evidence related to telemedicine in supporting the referral process for non-communicable disease cases in areas with limited access. Outcomes and supporting implementation are reported. Method: A scoping review was employed based on the PCC (Population, Concept, Context) framework. A literature search was conducted on PubMed, Scopus, ScienceDirect, and Google Scholar for Indonesian or English-language articles published in the period 2019–2025. The selection process followed the PRISMA-ScR guidelines through screening stages of titles, abstracts, and full texts. Source quality assessment was carried out descriptively in accordance with the objectives of the scoping review without excluding studies based on risk of bias. The selection and assessment process were carried out by two reviewers independently, with differences resolved through discussion. Data synthesis was carried out narratively. Results: Of the 354 articles identified, 10 studies met the inclusion criteria. Telemedicine was reported to expedite the referral process through triage and remote specialist consultation. Key findings include 81.8% of patients recommended for referral were referred within ≤48 hours after a tele-ECG consultation, a mean specialist response time of 4 days for the eConsult service, and a 25.4-day reduction in outpatient waiting time in the quantitative study. Improved referral quality was primarily related to the completeness of clinical data and the accuracy of referral decisions. However, effectiveness is influenced by infrastructure readiness, coordination between facilities, and human resource competency. Conclusion: Telemedicine has been used in various forms to support the referral process, but evidence remains limited and scattered across specific settings.